Principles of TQM and Its Role in Mohamed Khiedher University Performance, Baskara-Algeria - Bin Aieshi Bashier; Bin Aieshi Ammar (University of Science and Technology, Yemen, 2014)
Principles of TQM and Its Role in Mohamed Khiedher University Performance, Baskara-Algeria Abstract:    The aim of this study is to identify the principles of Total Quality Management and the role they play in evaluating the performance in Mohamed Khieder University, Biskra. In order to achieve this aim, the two researchers have designed a questionnaire, and it has been distributed over the study sample, 105 members among the faculty staff at Mohamed Khieder University, Biskra, Algeria. Depending on the data and on analyzing the results using the statistical program SPSS, the study found the following: -   The questioned teachers agree that the university (college) is applying the principles of total quality management. -   Applying the principles of total quality management does improvement the inputs quality and the operations quality and the outputs quality.   -   There is a relation between the principles of total quality management (spreading the quality culture, top management commitment, training, continuous improvement) and the inputs quality and the operations quality and the outputs quality in the institution under study. Key words: quality, total quality management, performance evaluation, high education institutions.